The interplay of cellular senescence and reprogramming shapes the biological landscape of aging and cancer revealing novel therapeutic avenues - Ding, Fuan; Yu, Ying; Zhao, Jiangqi; Wei, Shibo; Zhang, Yan; Han, Jung Ho; Li, Zhuo; Jiang, Hong-Bo; Ryu, Dongryeol; Cho, Minkyoung; Bae, Sung-Jin; Park, Wonyoung; et al. (Frontiers in Cell and Developmental Biology, 2025)
Cellular senescence and cellular reprogramming represent two fundamentally intertwined processes that profoundly influence aging and cancer. This paper explores how the permanent cell-cycle arrest of senescent cells and the identity-resetting capacity of reprogramming jointly shape biological outcomes in later life and tumor development. We synthesize recent findings to show that senescent cells, while halting the proliferation of damaged cells, can paradoxically promote tissue dysfunction and malignancy via their secretory phenotype. Conversely, induced reprogramming of somatic cells—exemplified by Yamanaka factors—resets cellular age and epigenetic marks, offering a potential to rejuvenate aged cells. Key findings highlight shared mechanisms (e.g., DNA damage responses and epigenetic remodeling) and bidirectional crosstalk between these processes: senescence signals can facilitate neighboring cell plasticity, whereas reprogramming attempts can trigger intrinsic senescence programs as a barrier. In aging tissues, transient (partial) reprogramming has been shown to erase senescence markers and restore cell function without inducing tumorigenesis, underlining a novel strategy to combat age-related degeneration. In cancer, we discuss how therapy-induced senescence of tumor cells may induce stem-cell-like traits in some cells and drive relapse, revealing a delicate balance between tumor suppression and tumor promotion. Understanding the interplay between senescence and reprogramming is crucial for developing innovative therapies. By targeting the senescence–reprogramming axis–for instance, via senolytic drugs, SASP inhibitors, or safe reprogramming techniques–there is significant therapeutic potential to ameliorate aging-related diseases and improve cancer treatment. Our findings underscore that carefully modulating cellular senescence and rejuvenation processes could pave the way for novel regenerative and anti-cancer strategies.